PENGARUH KECEMASAN MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA RANAH KOGNITIF PADA MATERI BENTUK ALJABAR SISWA KELAS VII - Dimas Femy Sasongko; Afiah Putri Yuliandani (Galois: Jurnal Penelitian Pendidikan Matematika, 2026)
Background: Mathematics anxiety is one of the psychological factors that may affect students' success in learning mathematics. Students who experience mathematics anxiety often have difficulty concentrating, lack self-confidence, and show lower academic achievement. Therefore, identifying students' mathematics anxiety levels and examining their relationship with learning outcomes are essential for improving mathematics instruction.. Objectif This study aimed to determine the mathematics anxiety levels of seventh-grade students and examine the effect of mathematics anxiety on cognitive mathematics learning outcomes in algebraic expressions. Methods : This study employed a quantitative approach using an ex post facto research design. The population consisted of 286 seventh-grade students at SMP Negeri 13 Malang, Indonesia. A sample of 32 students was selected using cluster random sampling. Data were collected through a mathematics anxiety questionnaire and a mathematics achievement test. The data were analyzed using descriptive statistics and simple linear regression. Results:The findings showed that 18.75% of students experienced low mathematics anxiety, 53.13% moderate anxiety, and 28.12% high anxiety. Simple linear regression analysis revealed that mathematics anxiety had a significant negative effect on students' learning outcomes (p = 0.006 < 0.05). The regression equation was Y = 7.928 − 0.062X, with a correlation coefficient (R) of 0.476 and a coefficient of determination (R²) of 0.226, indicating that mathematics anxiety explained 22.6% of the variance in mathematics learning outcomes. Conclusion: Most students experienced a moderate level of mathematics anxiety. Furthermore, mathematics anxiety had a significant negative effect on cognitive mathematics learning outcomes. These findings suggest that reducing students' mathematics anxiety should become an important consideration in designing effective mathematics learning strategies.